PENGARUH STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PERBANKAN DI INDONESIA - Hikalmi; andirfa, mulia; irfan; Muhammad Rizky Albayhaqi (JAKTABANGUN: Jurnal Akuntansi & Pembangunan, 2022)
This study aims to examine the effect of capital structure and firm size on the value of banking firms in Indonesia. The data used in this study is secondary data as many as 32 samples by accessing the official website of the financial services authority using a purposive sampling method. The method used to analyze the independent variable and the dependent variable is the multiple linear regression method and the classical assumption test. The results of the study partially that capital structure has no effect on the value of banking firms in Indonesia for the 2017-2020 period and firm size has a significant effect on the value of banking firms in Indonesia for the 2017-2020 period. Simultaneously shows that the capital structure and size of the company have a significant effect on the value of banking companies in Indonesia for the 2017-2020 period.